TINJAUAN PERANCANGAN BUKU ILUSTRASI UNTUK MENINGKATKAN EMPATI ANAK REMAJA MENGENAI SPEKTRUM AUTISME - Hamdi, Muhammad Zaidan; Karnita, Rosa (Kartala, 2025)
Autism Spectrum Disorder (ASD) is a developmental disorder, especially during childhood, that affects a person’s ability to engage in social interactions, exhibit appropriate behavior, and communicate effectively. Children with ASD are often misunderstood in social environments, leading to stigma and inappropriate treatment. This study aims to explore the perceptions of society, particularly adolescents, and provide a deeper understanding while raising awareness and empathy. The research uses a mixed-method approach, incorporating surveys and interviews to gather insights and firsthand experiences from respondents, as well as a case study analysis of the illustrated book "Kado Alma untuk Dila." The data obtained were analyzed to identify general perceptions, stigma, and potential effective educational methods. The results indicate that while adolescents are aware of ASD, their understanding is still limited, causing children with ASD to be marginalized in their social environments. However, adolescents express a strong desire to understand children with ASD better. Illustrated books, combining educational elements with entertainment, can effectively communicate information about autism to adolescents. Based on these findings, the follow-up will be the design of an illustrated book concept, which is expected to serve as an engaging educational tool for adolescents, promoting empathy and encouraging social inclusion for individuals with autism in everyday life.